Piecing together the puzzle of cutaneous mosaicism - Paller, Amy S. (American Society for Clinical Investigation, 2004)
Autosomal dominant disorders of the skin may present in a pattern following the lines of embryologic development of the ectoderm. In these cases, the surrounding skin is normal, and molecular studies have shown that the causative mutation is confined to the affected ectodermal tissue (type 1 mosaicism). Rarely, an individual shows skin lesions that follow the pattern of type 1 mosaicism, but the rest of the skin shows a milder form of the disorder (type 2 mosaicism). A new study provides the molecular basis for type 2 mosaicism .